Philippine Intellectual Property Rights under the World Trade Organization, 1995-2005: Implementing the Flexibilities under a TRIPs- Plus Commitment - Cabilo, Zuraida Mae D. (Kasarinlan: Philippine Journal of Third World Studies, 2011)
More than ten years since the Philippines acceded to the General Agreement on Tariffs and Trade-World Trade Organization (GATT-WTO), a review of the Philippine commitments to the treaty is yet to be done. This paper inquires on how commitments to the WTO have altered the Philippine intellectual property regime. It examines how the Philippines implemented its commitments to the Agreement on Trade–Related Intellectual Property Rights (TRIPs) in particular, and how the country is able to maximize the flexibilities provided under the TRIPs. This paper argues that while TRIPs may have been a project of the industrialized world with the support of key and influential industries to protect their corporate interests, the flexibilities offered by the agreement to developing and least-developed countries can be used to benefit public interest, particularly in the area of public health policy. In so doing, it is imperative upon the government to institute changes in its policy regime to make its existing intellectual property system responsive to public interest. Focus will be made on the implementation of flexibilities through legislation that intends to provide quality and affordable medicines as a matter of public health policy.
Keywords: WTO · GATT · TRIPs · Intellectual Property Code · Philippine intellectual property · public health policy